Supply chain management European perspectives - Koster, M. B. M. de, 1958-; Delfmann, Werner (Copenhagen Business School Press, 2005)
The popularity of Supply Chain Management in theory and practice is still increasing. This book provides a unique overview of current research trends and practices in the field from European scholars. Departing at selected theoretical inquiries on prominent concepts and methodologies in the supply chain field (e.g. theoretical foundations, 4PL concept, configurational approaches), the contributions in this volume cover highly relevant topics along a generic supply chain - upstream activities relating to modularisation, the development of logistical capabilities, but also order-picking optimization in warehouses, distribution network design heuristics and issues of urban freight transportation operations are among the topics treated. The methodologies employed intendedly reflect the variety of long-standing European research traditions and range from state-of-the art quantitative modelling to intriguing theoretical advances. The book is aimed at scholars and senior students interested in the SCM field as well as at the interested practitioner. -- Publisher description.
Keywords: Business logistics.; Industrial management.; elektronické knihy; electronic books